2018
DOI: 10.3847/1538-4357/aac2e6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Earth-directed Coronal Mass Ejections on the Sun’s Shadow Observed by the Tibet-III Air Shower Array

Abstract: We examine the possible influence of Earth-directed coronal mass ejections (ECMEs) on the Sun’s shadow in the 3 TeV cosmic-ray intensity observed by the Tibet-III air shower (AS) array. We confirm a clear solar-cycle variation of the intensity deficit in the Sun’s shadow during ten years between 2000 and 2009. This solar-cycle variation is overall reproduced by our Monte Carlo (MC) simulations of the Sun’s shadow based on the potential field model of the solar magnetic field averaged over each solar rotation p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Studies as we present here, without including detector effects, are still desirable, as this is the best way to find effects that arise from the magnetic field. The influence of coronal mass ejections (CMEs) on the cosmic-ray Sun shadow seen by different experiments is also something that can be studied, as has been shown in [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies as we present here, without including detector effects, are still desirable, as this is the best way to find effects that arise from the magnetic field. The influence of coronal mass ejections (CMEs) on the cosmic-ray Sun shadow seen by different experiments is also something that can be studied, as has been shown in [43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies as we present here, without including detector effects, are still desirable, as this is the best way to find effects that arise from the magnetic field. The influence of coronal mass ejections (CMEs) on the cosmic-ray Sun shadow seen by different experiments is also something that can be studied, as has been shown in [43]. Toward a complete model of transport and interaction Furthermore, adding particle interactions in the solar corona and in the Earth's atmosphere to the simulations will be another step that would increase our understanding of the phenomenon of cosmic-ray shadowing.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the Moon shadow observed by HAWC, the Sun shadow at low energies (∼1 TeV) is less significant due to the effect of the solar magnetic fields [64,65]. The Sun shadow is more pronounced at higher energies, at which the cosmic rays are less deflected by the coronal and interplanetary magnetic fields [71][72][73]. The evolution of the shadow size with energy is also an illustration of the angular resolution of the detector to cosmic rays, which has been modeled and verified in Refs.…”
Section: Sky Maps and Background Estimationmentioning
confidence: 97%
“…If the gamma-ray spectrum measured in the last solar minimum continues into the TeV range without a cutoff during the minimum of cycle 25, HAWC will be able to detect it with high significance. Long term monitoring from HAWC on the Sun shadow will also allow us to understand the effect of solar magnetic fields on TeV cosmic rays [71][72][73]. Finally, hadronic cosmic rays interacting in the solar atmosphere will also produce solar atmospheric neutrinos [48][49][50], which are being searched for in IceCube [82].…”
Section: B Implications and Future Workmentioning
confidence: 99%
“…In 2013, the Tibet AS-γ Collaboration compared coronal magnetic field models using the cosmic-ray Sun shadow at a median primary cosmic-ray energy of ∼10 TeV [8]. Later, they also studied the influence of solar coronal mass ejections (CMEs) on the cosmic-ray Sun shadow at energies of ∼3 TeV [9] and concluded that Earth-directed CMEs (ECMEs) affect the cosmic-ray Sun shadow at these energies. The influence of the solar magnetic field on the cosmic-ray Sun shadow has been studied by several other experiments, like Milagro, ARGO-YBJ, and HAWC, as well [10][11][12].…”
Section: Introductionmentioning
confidence: 99%